The Potential Role of Intensity-modulated Proton Therapy in the Regional Nodal Irradiation of Breast Cancer: A Treatment Planning Study. Issue 1 (January 2020) - De Rose, F.; Cozzi, L.; Meattini, I.; Fogliata, A.; Franceschini, D.; Franzese, C.; Tomatis, S.; Becherini, C.; Livi, L.; Scorsetti, M.
Abstract: Aims: To investigate the role of intensity-modulated proton therapy (IMPT) for regional nodal irradiation in patients with breast carcinoma in comparison with volumetric-modulated arc therapy (VMAT). Materials and methods: A cohort of 20 patients (10 in the breast-conserving surgery group and 10 post-mastectomy patients with tissue expander implants) was investigated. Proton plans were also computed using robust optimisation methods. Plan quality was assessed by means of dose–volume histograms and scored with conventional metrics. Estimates of the risk of secondary cancer induction (excess absolute risk, EAR) were carried out, taking into account fractionation, repopulation and repair. Results: Concerning target coverage, the data proved a substantial equivalence of VMAT and IMPT: for example, coverage for the 50 Gy target, expressed in terms of V98%, was 47.8 ± 0.4, 47.6 ± 0.4, 47.3 ± 0.8, consistent with the objective of 47.5 Gy, for post-mastectomy patients for the three groups of patients. Also, the conformality of the dose distributions was similar for the two techniques, about 1.1, without statistically significant differences. Organ at risk planning aims were achieved for all structures for both techniques. The mean dose to the ipsilateral lung was 10.8 ± 1.1, 6.2 ± 0.8, 7.2 ± 1.0; for the contralateral lung was 3.2 ± 0.7, 0.3 ± 0.2, 0.4 ± 0.2; for the contralateral breast was: 3.1 ± 0.7, 0.3 ± 0.3 and 0.3 ± 0.3, whereas it was 3.9 ± 0.9, 0.4 ± 0.3 and 0.5 ± 0.5, respectively, for the heart for VMAT, IMPT and robust IMPT plans over the whole group of patients. Robust optimisation affected the near-to-maximum dose values for contralateral lung and breast, the mean dose for the heart and ipsilateral lung, with a deterioration ranging from 20 to 40% of the nominal value of IMPT plans (e.g. from 8.1 ± 6.4 to 11.4 ± 8.8 for the heart compared with 16.2 ± 5.2 for the VMAT plans). The numerical values of EAR per 10 000 patient-years were about one order of magnitude higher for VMAT than for IMPT for contralateral structures: 11.66 ± 2.01, 0.89 ± 0.80, 0.98 ± 0.77 for the contralateral breast and the three groups of plans, respectively; 14.31 ± 2.75, 1.42 ± 0.80, 1.78 ± 0.87 for the contralateral lung; and 34.86 ± 2.64, 18.85 ± 2.15, 20.98 ± 2.35 for the ipsilateral lung. Conclusion: IMPT with or without robust optimisation seems to be a potentially promising approach for the radiation treatment of breast cancer when nodal volumes should be irradiated. This was measured in terms of dosimetric advantage and predicted clinical benefit. In fact, the significant reduction in estimated EAR could add further clinical value to the dosimetric sparing of the organs at risk achievable with IMPT. Highlights: IMPT for breast with regional nodal irradiation was investigated. Target coverage was fully achieved by both VMAT and IMPT plans. The sparing of the organs at risk was improved with IMPT. The estimated EAR per 10 000 patient-years was significantly higher for VMAT than for IMPT.